2021
DOI: 10.3390/ijms222212244
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Surgery after Neoadjuvant Targeted Therapies in Non-Small Cell Lung Cancer: A Narrative Review

Abstract: New drugs, including immune checkpoint inhibitors and targeted therapy, have changed the prognosis in a subset of patients with advanced lung cancer, and are now actively investigated in a number of trials with neoadjuvant and adjuvant regimens. However, no phase III randomized studies were published yet. The current narrative review proves that targeted therapies are safe in neoadjuvant approach. Unsurprisingly, administration of therapy is related to an acceptable toxicity profile. Severe adverse events’ rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
(165 reference statements)
1
4
0
Order By: Relevance
“…Judging from these data, the two schemes have little impact on the operation. A narrative review similar to our results suggests that neoadjuvant target therapy is well tolerated in resectable NSCLC patients, with all patients undergoing surgery without delay or major complications ( 27 , 28 ). Delays in surgery due to adverse events from oncology treatment, limitations in diagnostic services provided, and the possibility of progression during treatment may have challenged to the selection of neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Judging from these data, the two schemes have little impact on the operation. A narrative review similar to our results suggests that neoadjuvant target therapy is well tolerated in resectable NSCLC patients, with all patients undergoing surgery without delay or major complications ( 27 , 28 ). Delays in surgery due to adverse events from oncology treatment, limitations in diagnostic services provided, and the possibility of progression during treatment may have challenged to the selection of neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…It is important to consider whether there is any toxicity that may delay or prevent the efficacy of surgery during neoadjuvant therapy. Compared to neoadjuvant chemotherapy, the use of EGFR inhibitors has fewer severe respiratory adverse events (including pneumonitis and interstitial lung disease), which could limit the use of neoadjuvant therapy ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“… 81 , 82 Rare cases of severe respiratory adverse events (AEs) (including pneumonitis and interstitial lung disease) have been reported with some ALK, EGFR, and MET inhibitors, which could limit the use of these therapies before surgical resection. 83 , 84 Other reported rare toxicities that may impact surgery include the following: cardiotoxicity (osimertinib), 85 , 86 bradycardia (alectinib and crizotinib), 87 , 88 thrombocytopenia (osimertinib), 89 fever (dabrafenib plus trametinib), 90 hepatotoxicity (sotorasib), 91 and CNS toxicity (lorlatinib). 92 Preliminary results from the ALK -positive cohort of the NAUTIKA1 study demonstrated that neoadjuvant alectinib was well tolerated in patients with resectable NSCLC, and to date, all patients have undergone surgery without delays or major complications.…”
Section: Safety Considerations Of Neoadjuvant Ttsmentioning
confidence: 99%
“…The development of novel therapeutic strategies has remarkably enhanced the survival outcomes of patients with LUAD. [ 7–11 ] Immune checkpoint inhibitors (ICIs) targeting programmed cell death 1/ligand 1 (PD‐1/PD‐L1) can induce an effective antitumor role in these patients. [ 12,13 ] However, not all patients respond to ICIs, and their overall survival (OS) outcomes necessitate further improvement.…”
Section: Introductionmentioning
confidence: 99%